Relevansi Penerapan Metode Statistika secara Metodologis pada Skripsi Mahasiswa Program Studi Pendidikan Agama Islam - Dwi Yunitasari (Al-Munawwarah : Jurnal Pendidikan Islam, 2021)
There were discrepancies between applications of quantitative research, that is statistical methods, and qualitative research. In PAI Program, 26% of theses used quantitative research, and 74% qualitative. The cause was not known, but there were several reasons why this inequality should not be too big. First, sciences should always be approached, dissected, and analyzed using qualitative, quantitative, or mix-methods. Second, students' perceptions of statistics was in the good category, although there were only a few studies regarding this. For reducing this discrepancy, this study proposed to identify the relevance of applying statistical methods methodologically in research. This study used descriptive qualitative research. The data was thesis of S.1 PAI programm in UIN Walisongo Semarang 2020/2021 collected by census.There are irrelevance in applications of statistical methods. First, applications of simple linear regression analysis have 7 missinterpretation and analysis results were incomplete. Second, applications of correlation analysis have 5 misinterpretations, and analysis results were incomplete. Third, applications of multiple linear regression analysis have 2 missinterpretations, but analysis results were completed. Fourth, applications of central tendency have 1 misinterpretation, but analisis results were complete. Fifth, applications of Bar chart have 1 misinterpretation, and the chart anatomies were incomplete.